Intelligibility Redefinition and Students’ Confidence in English Speaking in Thai ELT - Singhanuwananon, Supatranut (European Journal of Sustainable Development, 2016)
One of the key aspects of speech is intelligible pronunciation (Derwing and Munro, 2009). As the use of English among non-native English speakers (NNSs) in international communication has grown rapidly, the British Received Pronunciation (RP) and the General American (GA) pronunciation models are doubted by non-native English teachers. The need of changes in pronunciation pedagogy and the definition of intelligibility in English as an International Language (EIL) which focuses on some, but not all of the elements of English pronunciation (Jenkins, 2002) are worth revisited, especially in the Thai context in which the focuses are strictly on the RP or GA principle, and this is defined as intelligible. The research questions examine the possibility of EIL model in English pronunciation pedagogy. The questions do not only seek possible changes, but also the effects on students’ confidence in using “imperfect English”. The research is designed to measure intelligibility based on EIL. The reason behind the focus of Thai technical students is that they are a group of students who are limitedly exposed to the language in their regular classes; inevitably have to use English speaking skills in their professions after graduation and entering the workforce. The findings show that, under the EIL model, unintelligible students defined by the Native Speaker model (NS) are not all or really unintelligible. The examination of the use of EIL model in pronunciation teaching and the effect of them on students of English should be proved to be useful and practical in ELT development in Thailand. This could be applied at an international level as well